Technological change, task complexity, and preferences for redistribution - David Hope; Julian Limberg; Nina Weber (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
Technological change has fundamentally transformed the US labour market in recent decades, with high-earning jobs becoming increasingly focused on nonroutine, complex tasks. We provide a first experimental test of whether fairness perceptions and preferences for redistribution differ when top earners gain their incomes through luck, routine work, or complex work. We find that the desired tax rate on top earners is up to 5.3 percentage points lower for the complex work treatment compared to the routine work treatment. Interestingly, performance on complex tasks is also more likely to be seen as the result of inherited intelligence.
Keywords: D31; D63; D91; H24; 330; Top income tax; technological change; redistribution; distributive preferences; fairness